Výzkum v didaktice cizích jazyků IV - Cox, Šárka (Masaryk University Press, 2021)
Title in English: Research in foreign language didactics IV This volume of proceedings is a result of a Specific Research project conducted in 2021 with the registration number MUNI/A/1239/2020 - Research on Learning and Teaching Foreign Languages. The contributions present the research studies of those doctoral students in the field of Foreign Language Didactics at the Faculty of Education of Masaryk University. The studies are written in Czech.